Analysis of Students' Mathematical Literacy Ability in Algebraic Concepts Based on Trends in International Mathematics and Science Study (TIMSS) Problems - Siregar, Erimson; Sutiarso, Sugeng; Yusuf, Zulhiyandi (Technium Social Sciences Journal, 2021)
This research uses descriptive qualitative. The aim is to examine students' mathematical literacy abilities and types of errors made by students of MTs Mathla’ul Anwar Kedondong in solving algebraic concept questions that were first accessed from TIMSS. The subjects of this study were all students of class VIII-A MTs Mathla’ul Anwar Kedondong, which had 30 students. The data was collected using tests and interviews. All student answers in the analysis of mathematical errors are based on empathy for students' mathematical literacy abilities, namely aspects of knowledge, application, and communication. Furthermore, for further analysis of the students 'mathematical errors, 2 students with the lowest scores were selected, representing the mathematical errors of all students based on the four aspects of the students' mathematical literacy abilities for interviews. The data analysis technique is by reducing data, presenting data, and drawing conclusions. The results of the analysis of the data collected, the mathematical literacy ability of students included in the medium category with an average score of 62.38 scores on a scale of 100. Based on the analysis of the mathematical literacy scheme capability mentioned, students can request solutions according to their needs and sufficient good at solving problems on the criminal aspect. However, judging from the mathematical mistakes made by students, students who made mistakes did not review the answers in solving the problems. This causes the problem solving is not correct.